Vous êtes sur la page 1sur 2

# 1) argue that the eigenvalues of

( )
,
j
x y
J are the same as that of
( ) j
z
J (namely: , ( 1) ,..., ( ) j j j .
Blah diddly blah blahsymmetry.
Generalize the result to
( )

j
u - J .
In order to preserve normalization, let
( )

j
u - J be related to
z
J by a unitary similarity transformation,

( )

j
z
U J U u - J [ .1]
Note that we know the eigenvalue relation, which we can front-multiply by U, and insert
1
U U U U

= = I , and having

( )

( )
j
z z
J m m m UJ U U m m U m U m m U m u = = - = J [ .2]
Note that this implies U m is an eigenket of the (Hermitian!) operator
( )

( )
j
u - J , with the same eigenvalues m .
2) Show that the zero operator can be written as,

?????
( )( ( 1) )( ( 2) )...( ) ( ) 0
m j
m j
J j J j J j J j J m
=+
=
= + = =
[
O [ .3]

( )

j
J u - J [ .4]
Do a unitary transform to the operator O to make the J into J
z
, as in [ .1], which can be done by inserting the identiy
operator

## U U = I at strategic points in [ .3] to get,

( ) ( )

( ) ( ) ( )
m j m j m j
z z
m j m j m j
U U U J m U U UU J m UU U J m
=+ =+ =+
= = =
= = = =
[ [ [
O O I I I I I [ .5]
Let the operator

z
U U = O O act on an arbitrary ket, and let us expand that ket in the (complete) eigenket basis jm ,
| | ( )
m j
z z z
m j
jm jm jm J m jm o o o
=+
=
' ' ' ' = =
[
O O [ .6]
In [ .6], we notice the appearance of a sort of complimentary Kronecker delta. Since j m j ' s s + , we can write the
operator eigenrelation,
( ) ( ) ( )(1 )
z mm
J m jm m m jm m m jm o
'
' ' ' ' ' = = [ .7]
Putting [ .7] into [ .6], and noting (1 ) 0
m j
mm
m j
o
=+
'
=

[
for j m j ' s s + , we immediately get,
| 0 0
z
jm jm o o ' ' = = O [ .8]
It is then trivial to undo the similarity transformation effected in [ .5],
| |

0 0 the zero operator
z
U U U U UU UU o o o o = = = = = O O IOI O O [ .9]
3) it follows from the result above that
2 1 j
J
+
is a linear combination of
0 1 2
, ,...,
j
J J J . Argue the same goes for
2
, 1, 2,...
j k
J k
+
=
huh? This seems useless. Its obvious that since
2 1 j
J
+
is block-diagonal, you of course have a J being a linear
combination of all the previous Js.
Answer: Do this by mathematical induction. Assume is true, and this implies the following, by
way of sum-index-fiddling,

[ .10]

The proof for follows from just repeating the same induction [ .10]. One of the steps looks a little
trickywhat is it meant when ????